DCAF13-mediated K63-linked ubiquitination of RNA polymerase I promotes uncontrolled proliferation in Breast Cancer - Zhi-Zhi Yang; Bing Yang; Haiyan Yan; Xingyu Ma; Bin Tian; Bingqi Zheng; Yong-Xian Chen; Yi-Ming Dong; Jinsi Deng; Ziling Zhan; Yanmei Shi; Jing Yuan Zhang; et al. (Nature Communications)
Abstract Hyperactivation of ribosome biogenesis (RiBi) drives cancer progression, yet the role of RiBi-associated proteins (RiBPs) in breast cancer (BC) is underexplored. In this study, we perform a comprehensive multi-omics analysis and reveal that assembly and maturation factors (AMFs), a subclass of RiBPs, are upregulated at both RNA and protein levels in BC, correlating with poor patient outcomes. In contrast, ribosomal proteins (RPs) do not show systematic upregulation across various cancers, including BC. We further demonstrate that the oncogenic activation of a top AMF candidate in BC, DCAF13, enhances Pol I transcription and promotes proliferation in BC cells both in vitro and in vivo. Mechanistically, DCAF13 promotes Pol I transcription activity by facilitating the K63-linked ubiquitination of RPA194. This process stimulates global protein synthesis and cell growth. Our findings uncover a modification of RPA194 that regulates Pol I activity; this modification is dysregulated in BC, contributing to cancer progression.